Extracorporeal membrane oxygenation for cardiogenic shock: a meta-analysis of mortality and complications - Sasa Rajsic; Benedikt Treml; Dragana Jadzic; Robert Breitkopf; Christoph Oberleitner; Marina Popovic Krneta; Zoran Bukumiric (Annals of Intensive Care, 2022)
Abstract Background Venoarterial extracorporeal membrane oxygenation (va-ECMO) is an advanced life support for critically ill patients with refractory cardiogenic shock. This temporary support bridges time for recovery, permanent assist, or transplantation in patients with high risk of mortality. However, the benefit of this modality is still subject of discussion and despite the continuous development of critical care medicine, severe cardiogenic shock remains associated with high mortality. Therefore, this work aims to analyze the current literature regarding in-hospital mortality and complication rates of va-ECMO in patients with cardiogenic shock. Methods We conducted a systematic review and meta-analysis of the most recent literature to analyze the outcomes of va-ECMO support. Using the PRISMA guidelines, Medline (PubMed) and Scopus (Elsevier) databases were systematically searched up to May 2022. Meta-analytic pooled estimation of publications variables was performed using a weighted random effects model for study size. Results Thirty-two studies comprising 12756 patients were included in the final analysis. Between 1994 and 2019, 62% (pooled estimate, 8493/12756) of patients died in the hospital. More than one-third of patients died during ECMO support. The most frequent complications were renal failure (51%, 693/1351) with the need for renal replacement therapy (44%, 4879/11186) and bleeding (49%, 1971/4523), bearing the potential for permanent injury or death. Univariate meta-regression analyses identified age over 60 years, shorter ECMO duration and presence of infection as variables associated with in-hospital mortality, while the studies reporting a higher incidence of cannulation site bleeding were unexpectedly associated with a reduced in-hospital mortality. Conclusions Extracorporeal membrane oxygenation is an invasive life support with a high risk of complications. We identified a pooled in-hospital mortality of 62% with patient age, infection and ECMO support duration being associated with a higher mortality. Protocols and techniques must be developed to reduce the rate of adverse events. Finally, randomized trials are necessary to demonstrate the effectiveness of va-ECMO in cardiogenic shock.